The Influence of Gynecological Malignancies and Patient Characteristics on Fall Risk Perception - Jingjing Gong; Lianhua Bai; Ying Zhang; Yuanyuan Liu; Xiaodan Li (IMR Press, 2024)
Background: The ability to predict how patient characteristics influence vulnerability for other potential health hazards would lead to more effective clinical preventions and better outcomes. In this study, we examined how gynecological malignancies and patient traits influence fall risk perception. Methods: Patients with gynecological cancers aged >18 years were surveyed using 5 tools: a predesigned questionnaire to collect general information (demographic characteristics and disease characteristics), the fall risk perception scale, the Morse fall risk assessment scale (Chinese), the Chinese Big Five Personality Inventory, and a medical coping strategy questionnaire. Results: Fall risk perception among patients with gynecological malignancies was scored 16.51 ± 17.647 (mean ± standard deviation (SD)) by the fall risk perception survey and 11.28 ± 15.270 (mean ± SD) by the Morse fall risk assessment scale. Multivariate linear regression analysis revealed that additional comorbidities, specific personality traits, and coping methods are positively correlated with patient perception of fall risk (p < 0.05). Conclusions: Patients with gynecological cancers have low perceived risk to fall, which is decreased further in specific subgroupings of patients lacking other chronic comorbidities, with neurotic personality traits, and who exhibit avoidant or submissive coping methods. These subgroups are good candidates for additional education designed to raise awareness of falling risk. This methodology can be applied to study the relationships between patient traits and other health hazards.